Stimulating the development of national Streptococcus suis guidelines in Viet Nam through a strategic research partnership - Peter Horby; Heiman Wertheim; Nguyen Hong Ha; Nguyen Vu Trung; Dao Tuyet Trinh; Walter Taylor; Nguyen Minh Ha; Trinh Thi Minh Lien; Jeremy Farrar; Nguyen Van Kinh
PROBLEM: Streptococcus suis is a common cause of adult bacterial meningitis in Viet Nam, and possibly other parts of Asia, yet this disabling infection has been largely neglected. Prevention, diagnosis and treatment are relatively straightforward and affordable but, in early 2007, no national diagnostic, case management or prevention guidelines existed in Viet Nam. APPROACH: Enhanced detection of S. suis infections was established in 2007 as part of a collaborative research programme between the National Hospital for Tropical Diseases, a key national hospital with very close links to the Ministry of Health, and a research group affiliated with Oxford University based in Viet Nam. The results were reported directly to policy-makers at the Ministry of Health. LOCAL SETTING: Viet Nam is a low-income country with a health-care system that has seen considerable improvements and increased autonomy. However, parts of the system remain fairly centralized the Ministry of Health. RELEVANT CHANGES: Following the improved detection and reporting of S. suis cases, the Ministry of Health issued guidance to all hospitals in Viet Nam on the clinical and laboratory diagnosis, treatment and prevention of S. suis. A public health laboratory diagnostic service was established at the National Institute of Hygiene and Epidemiology and training courses were conducted for clinicians and microbiologists. Ministry of Health guidance on surveillance and control of communicable diseases was updated to include a section on S. suis. LESSONS LEARNT: Research collaborations can efficiently inform and influence national responses if they are well positioned to reach policy-makers.